Toward Green Narrative: Management and the Evolutionary Epic - Starkey, Ken; Crane, Andrew (Academy of Management Review, 2003)
We use a narrative perspective to explore the relevance of the sciences dealing with ecology for management theory and practice, presenting the issues of ecoscience from the perspective of green narrative, based on the “evolutionary epic.” Adopting an interpretive sensemaking perspective on narrative, we address the narratological basis of the evolutionary epic and examine the potential for the narrative to inform a new relationship between management and the natural environment. We suggest implications for management theory and practice by examining elements of the narrative.